Spiritual Meaning Making and Trauma Recovery: Evaluation of a Psycho-social Intervention for Earthquake Survivors in Turkey - Kizilgecit, Muhammed; Okan, Nesrullah; Demir, Yasin; Cinici, Murat; Temiz, Yunus Emre; Toprak, Fatma Betuel; Karabulut, Fuat (Springer, 2025)
This study sets out to develop a psycho-social model for assessing the effectiveness of spiritually oriented logotherapy for earthquake victims with PTSD following the 6 February 2023, Kahramanmara & scedil; earthquake in Turkey. The findings of this study will undoubtedly contribute to the development of post-disaster spiritual support services. We developed and implemented a six-week Psycho-Social Training Programme through Spiritually Oriented Meaning in the cities of Malatya, Elaz & imath;& gbreve; and Kahramanmara & scedil;, which were significantly affected by the earthquake. A randomised controlled trial (RCT) design was used, with participants randomly assigned to either the intervention group or the control group. Pre-test and post-test assessments were conducted to evaluate the programme's impact. The findings were clear: the programme significantly reduced PTSD symptoms (p < .05), proving the effectiveness of a meaning-oriented approach in the survivors' healing process. Additionally, the programme made a positive contribution to spiritual support services and provided a model to meet post-disaster psychological needs. This programme demonstrated its potential as an effective method for addressing PTSD and enhancing spiritual recovery in earthquake survivors.
Keywords: Post-traumatic stress disorder (PTSD); Spiritually oriented logotherapy; Psycho-social support; Earthquake victims; Meaning focussed healing